2003
DOI: 10.1038/nm887
|View full text |Cite
|
Sign up to set email alerts
|

Original antigenic sin and apoptosis in the pathogenesis of dengue hemorrhagic fever

Abstract: Dengue virus presents a growing threat to public health in the developing world. Four major serotypes of dengue virus have been characterized, and epidemiological evidence shows that dengue hemorrhagic fever (DHF), the more serious manifestation of the disease, occurs more frequently upon reinfection with a second serotype. We have studied dengue virus-specific T-cell responses in Thai children. During acute infection, few dengue-responsive CD8+ T cells were recovered; most of those present showed an activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
689
5
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 719 publications
(745 citation statements)
references
References 34 publications
33
689
5
10
Order By: Relevance
“…The level of T cell response is thought to correlate to disease severity. 56,57 Mongkolsapaya and colleagues in Thailand showed that T cells in severe infection have a relatively low affinity for the current infecting serotype but a high affinity for a past infection with a different serotype, i.e. they display characteristics of original antigenic sin.…”
Section: The Cellular Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The level of T cell response is thought to correlate to disease severity. 56,57 Mongkolsapaya and colleagues in Thailand showed that T cells in severe infection have a relatively low affinity for the current infecting serotype but a high affinity for a past infection with a different serotype, i.e. they display characteristics of original antigenic sin.…”
Section: The Cellular Immune Responsementioning
confidence: 99%
“…they display characteristics of original antigenic sin. 57 Moreover, T cell responses in severe patients are mainly mono-functional in that they produce IFN- and/or TNF-α only and rarely CD107a, a marker of cytotoxic degranulation. Conversely, in patients with uncomplicated dengue, relatively more CD8 + T cells expressed CD107a and only a few expressed only IFN- and/or TNF-α.…”
Section: The Cellular Immune Responsementioning
confidence: 99%
“…Thus, structural criteria rather than primary sequences may dictate the TCR recognition of different antigenic epitopes, which makes it exceedingly difficult to predict the crossreactive nature of TCRs. 7,23,35,36 Crossreactivity of alloreactive T cells It is well known that the frequency of T cells in the periphery that can respond to transplant antigens is astonishingly high, even without prior exposure to donor antigens. 1,2 For example, it is estimated that about 0.1-1% of the peripheral T cells are responsive to alloantigens, and this responder frequency is several logs higher than the precursor frequency to nominal antigens in naive individuals.…”
Section: Specificity and Plasticity Of Tcrsmentioning
confidence: 99%
“…Immunization with one dengue virus is protective against future challenge with the immunizing virus. However, immunity built up after infection by one dengue virus protects only modestly or even negatively against reinfection by the other dengue viruses [6][7][8]. In particular, the risk of dengue hemorrhagic fever from one of the dengue viruses during a secondary infection appears to rise significantly if there was a previous primary infection from one of the other dengue viruses [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the risk of dengue hemorrhagic fever from one of the dengue viruses during a secondary infection appears to rise significantly if there was a previous primary infection from one of the other dengue viruses [4,6,9]. This 'original antigenic sin' implies that an effective vaccine for dengue must induce protective immunity against all four dengue viruses [1,6,7,10]. To date, no such vaccine has been developed.…”
Section: Introductionmentioning
confidence: 99%